Caffeine inhibits the activation of hepatic stellate cells induced by acetaldehyde via adenosine A2A receptor mediated by the cAMP/PKA/SRC/ERK1/2/P38 MAPK signal pathway. - He Wang; Wenjie Guan; Wanzhi Yang; Qi Wang; Han Zhao; Feng Yang; Xiongwen Lv; Jun Li (PLoS ONE, 2014)
Unlabelled Hepatic stellate cell (HSC) activation is an essential event during alcoholic liver fibrosis. Evidence suggests that adenosine aggravates liver fibrosis via the adenosine A2A receptor (A2AR). Caffeine, which is being widely consumed during daily life, inhibits the action of adenosine. In this study, we attempted to validate the hypothesis that caffeine influences acetaldehyde-induced HSC activation by acting on A2AR. Acetaldehyde at 50, 100, 200, and 400 μM significantly increased HSC-T6 cells proliferation, and cell proliferation reached a maximum at 48 h after exposure to 200 μM acetaldehyde. Caffeine and the A2AR antagonist ZM241385 decreased the cell viability and inhibited the expression of procollagen type I and type III in acetaldehyde-induced HSC-T6 cells. In addition, the inhibitory effect of caffeine on the expression of procollagen type I was regulated by A2AR-mediated signal pathway involving cAMP, PKA, SRC, and ERK1/2. Interestingly, caffeine's inhibitory effect on the expression of procollagen type III may depend upon the A2AR-mediated P38 MAPK-dependent pathway. Conclusions Caffeine significantly inhibited acetaldehyde-induced HSC-T6 cells activation by distinct A2AR mediated signal pathway via inhibition of cAMP-PKA-SRC-ERK1/2 for procollagen type I and via P38 MAPK for procollagen type III.